Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
- w = 3
- v = 5
Step-by-step explanation:
Given:
- 3v = 5w
- 6v + 18 = 16w
3v = 5w
=> 3v/5 = w
6v + 18 = 16w
=> 6v + 18 = 16(3v/5)
=> 6v + 18 = 48v/5
=> 6v + 18 = 9.6v
=> 18 = 3.6v
=> v = 5
Let's refer back to our equation '3v = 5w'.
=> 3v = 5w
=> 3(5) = 5w
=> 15 = 5w
=> w = 3
Therefore, our answer is (v = 5; w = 3).
Hoped this helped.
[tex]3v = 5w ~~~....(i)\\\\6v +18 = 16w~~~ ....(ii)\\\\\text{From (i):}\\\\3v = 5w\\ \\\implies 2(3v) =2(5w) \\\\\implies 6v = 10w ~~~......(iii)\\\\(ii) - (iii):\\\\6v + 18 -6v = 16w -10w\\\\\implies 18 = 6w\\\\\implies w = \dfrac{18}6 = 3[/tex]
[tex]\text{Substitute w =3 in equation (iii):}\\\\6v = 10(3) = 30\\\\\implies v =\dfrac{30} 6 = 5\\\\\\\text{Hence}~ v= 5 , ~w= 3[/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.